Designing Electronic Structures of Multiscale Helical Converters for Tailored Ultrabroad Electromagnetic Absorption - Zhaobo Feng; Chongbo Liu; Xin Li; Guangsheng Luo; Naixin Zhai; Ruizhe Hu; Jing Lin; Jinbin Peng; Yuhui Peng; Renchao Che (Nano-Micro Letters)
Highlights The energy conversion mechanism is thoroughly analyzed, with a detailed quantitative characterization of the dissipation capacities of polarization, conduction, and magnetic loss. Inspired by DNA transcription, atom and geometry configurations co-modulating multi-scale helical converters achieve the RL min of −63.13 dB at 1.29 mm, and the maximum RCS reduction value reach 36.4 dB m2. Orbital coupling, spin and cross polarization synergize to realize a 6.08 GHz EAB, further expanding to ultrabroad electromagnetic wave absorption of 12.16 GHz through metamaterial design.